Manpower Planning Based on Digital Economy Horticultural Agriculture Sector in Cianjur Regency, West Java Province - Gatiningsih Gatiningsih; Ika Sartika; Etin Indrayani; Sadu Wasistiono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyzegovernment policies in development planning based on the industrial revolution 4.0 (RI 4.0), analyzing labor planning for the horticultural agricultural sector based on RI 4.0 and formulating scenarios for planning for the horticultural agricultural sector based on RI 4.0. This type of research is exploratorywith a qualitative approach the data were collected through interviews. The research informants are the head of farmer groups, managers of private farms, department heads and academics. Informants were selected purposively with certain criteria. Data were analyzed usingTAIDA (Tracing, Analyzing, Imaging, Deciding and Acting). The results of this study found thatThe policy for implementing RI 4.0 has not been accommodated in district regional planning documents, as well as for labor planning for the agricultural sector, especially for horticulture based on RI 4.0, it has not been accommodated in either the RPJMD or Strategic Plan. The workforce requirement for the 2021-2024 period is 12,028 people. The largest proportion of labor absorption is at the maintenance stage 44.02% and the lowest is 0.69% in marketing. The implementation of RI 4.0 still considers social, technical and physical aspects. Mondy's theory needs to be sharpened per cultivation stage so that the reduction in labor can be suppressed. Suggestions, the policy for implementing RI 4.0 is contained in the RPJMD and the Strategic Plan of each service, it is necessary for the role of inter-regional government institutions in planning the workforce of the industrial revolution 4.0.